The role of O-glycosylation in human disease. (June 2021) - Magalhães, Ana; Duarte, Henrique O.; Reis, Celso A.
Abstract: O-glycosylation is a highly frequent post-translation modification of proteins, with important functional implications in both physiological and disease contexts. The biosynthesis of O-glycans depends on several layers of regulation of the cellular glycosylation machinery, being organ-, tissue- and cell-specific. This review provides insights on the molecular mechanism underlying O-glycan biosynthesis and modification, and highlights illustrative examples of diseases that are triggered or modulated by aberrant cellular O-glycosylation. Particular relevance is given to genetic disorders of glycosylation, infectious diseases and cancer. Finally, we address the potential of O-glycans and their biosynthetic pathways as targets for novel therapeutic strategies. Highlights: O-glycosylation is a highly regulated process with key roles in health and disease. Defects affecting the O-glycan biosynthetic machinery impact several human diseases. O-glycans are key modulators of host-pathogen interplay and immune response. Aberrant cellular O-glycosylation promotes oncogenic signaling and tumor progression. O-glycans represent promising molecular targets for innovative therapeutic approaches.